PENGARUH STICKER PICTURE TERHADAP MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK RAUDHATUL JANNAH PASAMAN BARAT - Laila Pitra Maharani; Dadan Suryana; Elise Muryanti; Vivi Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of early reading skills among children aged 5–6 years at TK Raudhatul Jannah Pasaman Barat, as indicated by difficulties in recognizing letters, distinguishing between similar letters, associating letter sounds with pictures, and reading simple words. The study aimed to examine the effect of using sticker picture media on children's early reading skills. This research employed a quantitative approach using a quasi-experimental design, involving Group B2 as the experimental class and Group B3 as the control class, selected through purposive sampling. Data were collected using an early reading skills test and analyzed through tests of normality, homogeneity, the Independent Samples t-test, and Effect Size (Cohen's d) using SPSS version 29. The results showed that the data were normally distributed and homogeneous. The Independent Samples t-test yielded a significance value (Sig. 2-tailed) of 0.000 (< 0.05), indicating a significant difference between the experimental and control groups. Furthermore, the Effect Size (Cohen's d) value of 2.20 indicated a very large effect. Therefore, it can be concluded that the use of sticker picture media has a positive and significant effect on the early reading skills of children aged 5–6 years at TK Raudhatul Jannah Pasaman Barat.